Energy related practices in Mediterranean low-income housing. Issue 1 (2nd January 2020) - Domínguez-Amarillo, Samuel; Fernández-Agüera, Jesica; Peacock, Andrew; Acosta, Ignacio
ABSTRACT: The development of policies to improve energy efficiency and the retrofitting of the existing housing stock requires adequate knowledge of the operation in practice and user needs. This becomes crucial when intervening in social housing, where household energy practices are likely to be confounded by energy affordability leading to outcomes that are distinct and sub-optimal when compared to those conventionally assumed. A field survey and analyses applied to more than 700 homes from collective social housing buildings in the south of Spain is reported here. The results show a clear stratification of energy consumption and ownership of household appliances and thermal systems. An austere self-imposed use of energy appears, coupled with normative adoption of certain energy-efficient habits particularly with respect to laundry. An emergence of multimedia and computer equipment seems to be changing the overall balance of use of equipment in homes. A clear income level above which provision of thermal comfort using mechanical means became affordable was found. The work provides useful data of home habits and identifies the main underperformance issues of this representative household-group, what may feed the design of upgrade policies and optimization of energy access for this housing stock.